Study on the catastrophic mechanism of slope instability induced by pore gas migration under severe drying-wetting alternation - Jianjun Dong; Mingxin Xu; Hao Jiang; Ke Gao (Scientific Reports)
Abstract Pore gas migration under severe drying-wetting alternation induces the instability of unsaturated soil slopes, the study of its catastrophic mechanism can be based on the effective stress equation and shear strength equation of unsaturated soil, the unsaturated permeability coefficients in unsaturated region can be computed in real time under unsaturated–saturated seepage condition, this approach, combined with field experiments and utilizing the embedded FISH language of FLAC3D, allows for numerical simulation analysis of slope safety and stability. Under severe drying-wetting alternation, when the soil body within the slope is unsaturated, pore gas will escape and air cushions will form, the zones of pore gas escape/formation of air cushions in unsaturated soil under severe drying-wetting alternation are statistically analyzed using the Weibull distribution. The study shows that the regions where pore gas escapes and air cushions form initially occur in the infiltration zone at the slope foot and gradually extend into the slope with the intensity of drying-wetting alternation increasing. Under conditions of no pore gas migration, pore gas escape and pore gas formation of air cushions, the factor of safety in all three cases decrease significantly with the intensity of drying-wetting alternation increasing; migration process results in a sharp decline in shear strength and an increased probability of soil slip. The study finds that the damage to slope hgstability caused by pore gas escape is greater than that caused by air cushions formation.